Combined chloroquine and ribavirin treatment does not prevent death in a hamster model of Nipah and Hendra virus infection - Freiberg, Alexander N. (Society for General Microbiology, 2010)
Hendra virus (HeV) and Nipah virus (NiV) are recently emerged, closely related and highly pathogenic paramyxoviruses that cause severe disease such as encephalitis in animals and humans with fatality rates of up to 75 %. Due to their high case fatality rate following human infection and because of the lack of effective vaccines or therapy, they are classified as Biosafety Level 4 pathogens. A recent study reported that chloroquine, an anti-malarial drug, was effective in preventing NiV and HeV infection in cell culture experiments. In the present study, the antiviral efficacy of chloroquine was analysed, individually and in combination with ribavirin, in the treatment of NiV and HeV infection in in vivo experiments, using a golden hamster model. Although the results confirmed the strong antiviral activity of both drugs in inhibiting viral spread in vitro, they did not prove to be protective in the in vivo model. Ribavirin delayed death from viral disease in NiV-infected hamsters by approximately 5 days, but no significant effect in HeV-infected hamsters was observed. Chloroquine did not protect hamsters when administered either individually or in combination with ribavirin, the latter indicating the lack of a favourable drug–drug interaction.